Disturbed mitochondrial redox state and tissue energy charge in cholestasis. Issue 9 (12th July 2021) - Ghanbarinejad, Vahid; Ommati, Mohammad M.; Jia, Zhipeng; Farshad, Omid; Jamshidzadeh, Akram; Heidari, Reza
Abstract: The liver is the primary organ affected by cholestasis. However, the brain, skeletal muscle, heart, and kidney are also severely influenced by cholestasis/cirrhosis. However, little is known about the molecular mechanisms of organ injury in cholestasis. The current study was designed to evaluate the mitochondrial glutathione redox state as a significant index in cell death. Moreover, tissue energy charge (EC) was calculated. Rats underwent bile duct ligation (BDL) and the brain, heart, liver, kidney, and skeletal muscle mitochondria were assessed at scheduled time intervals (3, 7, 14, and 28 days after BDL). A significant decrease in mitochondrial glutathione redox state and EC was detected in BDL animals. Moreover, disturbed mitochondrial indices were evident in different organs of BDL rats. These data could offer new insight into the mechanisms of organ injury and the source of oxidative stress during cholestasis and might provide novel therapeutic strategies against these complications. Abstract : Disturbed mitochondrial redox environment, mitochondrial dysfunction, and cellular energy crisis seem to play a fundamental role in the pathogenesis of cholestasis/cirrhosis‐associated organ injury. ΔΨ, mitochondrial membrane potential; ATP, adenosine triphosphate; BDL, bile duct ligation; GR, glutathione reductase; IMS, intermembrane space; mPT, mitochondrial permeability transition; ROS, reactive oxygen species Research Highlights: Cholestasis is a severe clinical complication that affects several organs There is no precise mechanism for cholestasis‐induced organ injury so far Our data indicate that mitochondrial impairment plays a fundamental role in cholestasis‐induced organ injury Mitochondrial impairment and energy crisis could lead to organ injury Targeting cellular mitochondria could serve as a potential therapeutic option in cholestasis